DAMPAK GLOBALISASI PASAR DAN PRODUKSI: DITENGAH LINGKUNGAN BISNIS NASIONAL - A.A. G Agung Artha Kusuma; KM Agus Satria Pramudana (Faculty of Economics and Business Udayana University, 2017)
A fundamental shift has happened in the economics and business world. Countries within the same region integrates one another consolidating their politics and economies creating a trading bloc as means for accelerating economic growth. This situation creates new market opportunities and access for low cost workers for producers, consequently generating multiple country of origin information in a single product. For consumers, in terms of evaluating a product, currently are experiencing a new shift, cognitively consumers separate the cue signaled from both country of design and country of manufacture. In this study, first is analysed the impact of strong image related concept that presents with fashion products toward purchase intention, from the test, result is concluded that perceived quality, brand awareness, and fashion involvement had positive correlation toward purchase intention. Second is analysed the role of both country of origin and consumer ethnocentrism that serve as the weak country image concept in moderating function, the outcome form the test concluded that country of origin and consumer ethnocentrism cannot influence the relationship of brand awareness, perceived quality, and fashion involvement toward purchase intention. In addition, based on the findings of this study, further discussed how the interaction between country’s image and brand image affecting purchase intention.